Electrochemical characterization of samples of commercial steel treated with acetylene plasma - Regone, Natal Nerimio [UNESP]; Pires de Souza, Maria Eliziane; Alvarenga Freire, Celia Marina; Ballester, Margarita; Rangel, Elidiane Cipriano [UNESP]; Cruz, Nilson Cristino da [UNESP] (Natl Inst Science Communication-niscair, 2020)
Cutting tools have been employed in wood processing must be corrosion and wear resistant due to the acidic composition of wood and the wear generated during cutting, which lead to the deterioration of steel saws. Hydrogenated amorphous carbon films possess mechanical, tribological and barrier properties that can increase the hardness, wear and corrosion resistance of this type of tool. This work has involved an investigation of the effectiveness of plasma-deposited amorphous carbon thin films in protecting commercial carbon steel saws. Before deposition, the substrates were sputter-cleaned in argon plasma (19.27 Pa; 50 W) for 180 s. The films have been deposited using acetylene and argon mixtures excited by a radio frequency power supply (13.56 MHz, 70 W). The concentration of acetylene in the mixture has been varied in the inverse proportion to that of argon so as to maintain a constant total gas pressure of 1.8 Pa. The deposition time was 3600 s. The chemical behavior of the coated saws have been evaluated by electrochemical impedance spectroscopy (EIS) and polarization curves.Surface images of the plasma-coated samples have been recorded by scanning electron microscopy (SEM). The results have indicated that the plasma treatment has increased the corrosion resistance of carbon steel samples in acidic solutions.
Keywords: Saw; Impedance; Polarization; Plasma enhanced chemical vapor deposition (PECVD)